The Potential of the ICUC® Documentation Concept to Improve Trauma Surgery - Regazzoni, P; Dell'oca, A A Fernandez; Perren, S M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2017)
Conventional documentation of surgical procedures using only pre- and postoperative X-ray images and possibly a few intra-operative pictures does not allow secondary analysis of the technical performance in detail. In particular, the quality of the handling of tissues and surgical tools cannot be judged «post hoc», i.e. after the end of the surgical procedure. The invasiveness of the surgical act cannot yet be quantified. Surrogate invasiveness indices have therefore been developed. Furthermore, conventional documentation does not allow evaluation of the proper use of the C-arm both technically and with regard to fluoroscopy time. Documentation that follows the ICUC® documentation concept includes all fluoroscopy shots and images covering all key portions of the entire surgical procedure by multiple still images or videos. In certain cases, such documentation can help to explain post-operative courses that might be difficult to understand based only on X-rays and written operation reports. Finally, the data included in ICUC® documentation are a valuable source for knowledge extraction. In addition, time saving is conceivable if operation reports can include images of the key stages of the procedure with a few additional comments dictated during the surgery. Key words: trauma surgery, ICUC® documentation concept.
Keywords: Wounds and Injuries; fluoroskopie; Surgical Procedures, Operative; Fluoroscopy; Humans; Documentation; lidé; chirurgie operační; rány a poranění; dokumentace